The influence of efficiency and effectiveness in the utilization of school operational assistance funds on the quality of teaching and learning services: A Case study at SMP Negeri 12 Mimika and SMP Negeri Naena Muktipura - Fitri Dyan Agustin; Mesak Iek; Yundy Hafizriandra (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study examines the influence of efficiency and effectiveness in the use of School Operational Assistance (BOS) funds on the quality of teaching and learning services in Indonesia. This research focuses on two junior high schools in Papua—SMP Negeri 12 Mimika and SMP Negeri Naena Muktipura—which represent different demographic and resource contexts. Research/methodology: A mixed-method approach was applied, combining surveys, interviews, observations and document analysis. Quantitative data were tested using multiple linear regression, and qualitative insights were analyzed through content analysis. Results: Findings show that both efficiency (B = 0.670, p < 0.001) and effectiveness (B = 0.553, p < 0.001) in BOS fund utilization significantly improve the quality of teaching and learning. SMP Negeri 12 Mimika demonstrated higher efficiency, effectiveness, and overall service quality than SMP Negeri Naena Muktipura. BOS funds were used to enhance facilities, provide teaching aids, and support teacher training, although equitable access to training remained limited. Conclusions: Efficiency and effectiveness in BOS fund use are crucial for improving service quality, with efficient management exerting a stronger influence on facilities, teacher training, and learning tools. Transparent and well-targeted fund allocation is vital for improving educational outcomes. Limitations: This study was limited to two schools in Papua, potentially reducing its generalizability. Context-specific qualitative findings and time constraints also limited the perspectives of broader stakeholders. Contribution: This study adds to the educational finance and policy literature by showing how efficient and effective fund management enhances education quality in under-resourced settings, offering guidance for BOS policy improvements and school-level practices.